2021
DOI: 10.3389/fimmu.2021.674185
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Type 1 Porcine Reproductive and Respiratory Syndrome Virus With In Vitro Derived Conventional Dendritic Cells

Abstract: The present study delineates the interaction of a typical PRRSV1.1 isolate 3267 (moderate virulence) with in vitro derived pig conventional dendritic cells, cDC1, cDC2, and a CD14+ population (designated as CD14+ DCs). cDC1 and cDC2 were not susceptible to 3267 infection, but a fraction of CD14+ DCs were infected. After exposure to the virus, all three DC types remained immature as determined by no increase of maturation molecules (MHC-I, MHC-II, CD80/86, CCR7), no release of cytokines, no modification of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Exposure of pDCs to PRRSV did not significantly inhibit the natural capability of these cells to produce IFN-α except for some PRRSV2 strains, including the highly pathogenic PRRSV2 that emerged in China in 2006 and the highly virulent PRRSV1.3 Lena strain. When pDCs were exposed to infected macrophages, the IFN-α production was higher than that obtained when using cell-free virions ( 73 ), similar to what has been reported recently for cDCs ( 56 ). Efficient sensing of infected macrophages by pDCs required integrin-mediated intercellular contact and intact actin filaments in the macrophages ( 73 ).…”
Section: Plasmacytoid Dendritic Cells Againts Prrsvsupporting
confidence: 87%
See 4 more Smart Citations
“…Exposure of pDCs to PRRSV did not significantly inhibit the natural capability of these cells to produce IFN-α except for some PRRSV2 strains, including the highly pathogenic PRRSV2 that emerged in China in 2006 and the highly virulent PRRSV1.3 Lena strain. When pDCs were exposed to infected macrophages, the IFN-α production was higher than that obtained when using cell-free virions ( 73 ), similar to what has been reported recently for cDCs ( 56 ). Efficient sensing of infected macrophages by pDCs required integrin-mediated intercellular contact and intact actin filaments in the macrophages ( 73 ).…”
Section: Plasmacytoid Dendritic Cells Againts Prrsvsupporting
confidence: 87%
“…Recently, Li and Mateu ( 56 ), using in vitro derived cDCs, also proved the non-susceptibility of cDC1 and cDC2. This work further revealed that cDC1 and cDC2 remained immature upon PRRSV inoculation concerning the expression of maturation molecules, cytokine production, and the endocytosis/phagocytosis capabilities.…”
Section: Response Of Conventional Dcs Against Prrsvmentioning
confidence: 97%
See 3 more Smart Citations